An estimated new keynesian dynamic stochastic general equilibrium model of the Euro area - Ratto, Marco; Roger, Werner; Veld, Jan in't 1962-; Girardi, Riccardo; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2005)
In recent years a new consensus has emerged in macroeconomics in general and in model building in particular, the so called New Keynesian Paradigm (NKM). This paper applies Bayesian estimation techniques to a time series data set of the euro area and presents estimates of a DSGE model. The purpose of this paper is not to estimate the current version of the QUEST model directly with these methods but rather to estimate a prototype new generation New-Keynesian DSGE model. This model can then serve as a benchmark for an estimation of a QUEST specification. In fact in some dimensions the QUEST model may need to be adjusted to come closer to a DSGE model.
Economic Papers